Pentecostals in the 21st century: identity, beliefs, praxis - Constantineanu, Corneliu; Scobie, Christopher J. (Cascade Books, 2018)
Introduction : Pentecostal identity, spirituality, and theology /Corneliu Constantineanu and Christopher J. Scobie --Pentecostal identity /Veli-Matti Kärkkäinen --Some aspects of hermeneutics in the Pentecostal tradition /Roger Stronstad --Sacrament or ordinance? : A Pentecostal approach to a contentious issue /Jean-Daniel Plüss --Towards a Pentecostal perspective on salvation /Edmund J. Rybarczyk --How, why, and when should someone be baptized? : What is its relationship to salvation? /Glenn Balfour --The baptism in the Holy Spirit /Frank D. Macchia --The gifts of the spirit /Keith Warrington --The church /Cecil M. Robeck Jr. --A Pentecostal proposal for discipleship /Christopher J. Scobie --Fulfillment of God's promise in the soon-to-return King /Van Johnson --Pentecostalism and ecumenism : past, present, and future /Amos Yong --The theological motivations for Pentecostal mission /Wonsuk Ma --Mission, education, and public engagement : a case study in Romanian Pentecostalism /Corneliu Constantineanu.